Journalistic Digital Literacy Training in Promoting Religious Moderation in Pesantren Cibiru District: Kesalehan Digital dan Moderasi Keagamaan: Negosiasi Otoritas Islam di Kalangan Santri di Sebuah Pesantren di Kabupaten Bandung - Shodiqin, Asep; Khosim, Ali; Iryana, Wahyu (jsd: Journal of Society and Development, 2025)
This study aims to analyze how digital piety among santri in Islamic boarding schools (pesantren) in Bandung Regency shapes the ecology of Islamic authority and influences diverse forms of religious moderation in everyday practice. This study is important because the digitalization of da‘wah has expanded santri’s religious references while simultaneously carrying the potential to generate polarization when not accompanied by adequate literacy and guidance. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with santri, observation of religious activities within the pesantren environment, and examination of relevant digital artifacts, such as religious content accessed and shared by participants. The data were analyzed using thematic analysis to identify patterns of religious practice, authority references, and emerging mechanisms of negotiation. The findings indicate that digital piety emerges as a structured religious routine through the consumption of short religious lectures, practices of saving and sharing content emphasizing ethical and moral values, and the curation of content perceived as “safe” and non-confrontational. Within a plural ecology of Islamic authority, kiai and pesantren teachers remain the final sources of religious legitimacy, while digital religious authorities function primarily as initial triggers of knowledge that are negotiated through account selection, interaction restraint, and cross-checking with pesantren authorities. As a result, religious moderation among santri appears more strongly as a lived social practice operating contextually between pesantren spaces and digital environments. The implications of this study highlight the importance of strengthening digital religious literacy, establishing accessible verification mechanisms, and developing pesantren-based content curation to reinforce religious moderation in the era of social media. The originality of this research lies in its articulation of the micro-level mechanism of “authority negotiation” as a bridge between digital piety and religious moderation, thereby offering both conceptual and empirical contributions to the fields of digital religion, Islamic authority, and religious moderation within pesantren contexts.